How Does Interleukin-22 Mediate Liver Regeneration and Prevent Injury and Fibrosis? - Muhammad Babar Khawar; Fareeha Azam; Nadeem Sheikh; Khawaja Abdul Mujeeb (Journal of Immunology Research)
Interleukin-22 (IL-22) is a pluripotent T cell-derived cytokine which is a member of IL-10 cytokine family. It is the only interleukin produced by immune cells but does not target immune system components. IL-22 is mainly produced by dendritic cells (DCs) and TH17, TH22, NK, and NKT cells and targets a number of body tissues including liver, pancreas, and other epithelial tissues. It provokes a series of downstream signaling pathways upon binding with IL-22R complex which protects liver damage through STAT3 activation. IL-22BP is an inhibitor of IL-22 which has 20–1000x more affinity to bind with IL-22 compared to IL-22R1 that inhibits IL-22 activity. Its level was found to be positively correlated with the severity of liver damage and fibrosis. So, the present review is an effort to reveal the exact mechanism lying in the hepatoprotective activity of IL-22 and some of its future therapeutic implications.